Saling Menanggung Beban: Model Kesehatan Mental Eklesial dalam Pencegahan Bunuh Diri - Donald Siwabessy (SAINT PAUL'S REVIEW, 2026)
Suicide is a complex global public health issue that cannot be adequately addressed through an individualistic approach alone. This article aims to develop an Ecclesial Mental Health Model for suicide prevention grounded in the theological principle of “bearing one another’s burdens” (Galatians 6:2). The study employs a qualitative approach using a literature review method, drawing on theological, pastoral, and contemporary mental health sources. The findings indicate that this principle possesses both normative and therapeutic dimensions, enabling a paradigm shift from an individual-centered pastoral approach toward a community-based model. The proposed model comprises six main components: a relational theological foundation, community structures as support networks, sustained pastoral functions, preventive mechanisms through education and early detection, spiritual practices, and the creation of stigma-free safe spaces. Overall, this model affirms that the church, as a relational community, holds a strategic role in fostering resilience, reducing social isolation, and strengthening holistic and integrative suicide prevention efforts.